Indonesian Medicinal Plants for Anticancer - Syazili Mustofa (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
The potential of Indonesia's natural wealth of plants to be developed as anticancer agents is enormous, thanks to its abundant biodiversity. Indonesia has become a